Effect of substrate miscut on the microstructure in epitaxial Pb(Mg1/3Nb2/3)O3-PbTiO3 thin films - Chekhonin, Paul; Mietschke, Michael; Pohl, Darius; Schmidt, Frank; Faeler, Sebastian; Skrotzki, Werner; Nielsch, Kornelius; Huehne, Ruben (Materials Characterization, 2017)
Pb(Mg1/3Nb2/3)O3-PbTiO3 is known for its excellent ferroelectric and electrocaloric properties. Epitaxial films, which allow applying high voltages, can be grown in a much broader parameter range when depositing them on miscut substrates than on those without miscut. To understand the influence of substrate miscut, here the structure and microstructure of two films, with and without miscut, is compared in detail. In both cases the epitaxial strain is relaxed, but while in films without miscut perfect misfit dislocations are observed, the film with miscut exhibits many partial dislocations and stacking faults. The stacking faults may play an important role for the stabilization of the pure perovskite Pb(Mg1/3Nb2/3)O3-PbTiO3 phase in thin films on miscut substrates.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Dislocation structure; Ferroelectric; Microstructure; PMN-PT; Stacking faults; Thin films